2007
DOI: 10.1007/s11664-006-0048-6
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Fatigue Behavior of the Near-Eutectic Sn-Ag-Cu Alloy between −25°C and 125°C

Abstract: When near-eutectic Sn-Ag-Cu (SAC) alloys are used to make soldered ballgrid-array (BGA) assemblies, the grain size of the joints is very large. During thermomechanical cycling, the solder joint fatigue process is often initiated with recrystallization of the Sn grains, resulting in a smaller grain size in the deformed areas. Grain boundary sliding and increased grain boundary diffusion then results in intergranular crack nucleation and propagation along the recrystallized Sn grain boundaries. In this work, fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…27,29 However, systematic isothermal cycling experiments led at most to very limited, local recrystallization near the crack tip. 24,[30][31][32][33][34] In fact, Korhonen et al 34 conducted isothermal cycling experiments on single-crystal Sn3.8Ag0.7Cu samples at different temperatures ranging from À 25°C to 125°C, reproducing the strains and dwell times common in thermal cycling, without creating significant recrystallization. Recrystallization occurred more readily in solder joints with lower Ag concentrations, and thus greater average spacing between the Ag 3 Sn precipitates.…”
Section: Recrystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…27,29 However, systematic isothermal cycling experiments led at most to very limited, local recrystallization near the crack tip. 24,[30][31][32][33][34] In fact, Korhonen et al 34 conducted isothermal cycling experiments on single-crystal Sn3.8Ag0.7Cu samples at different temperatures ranging from À 25°C to 125°C, reproducing the strains and dwell times common in thermal cycling, without creating significant recrystallization. Recrystallization occurred more readily in solder joints with lower Ag concentrations, and thus greater average spacing between the Ag 3 Sn precipitates.…”
Section: Recrystallizationmentioning
confidence: 99%
“…Indeed, an increase in low-temperature dwell time from 0.5 min to 15 min led to a significant reduction in solder joint life span, while extensions beyond that had little or no effect. 1 The absence of significant recrystallization in isothermal cycling at a temperature like 100°C or 125°C 34 suggests that dislocations created there are annihilated too quickly, or that a sufficiently dense cell structure on which dislocations can continue to multiply is never established. However, we suggest that a pre-existing dislocation structure established during the low-temperature dwell can help multiply and stabilize the high-temperature dislocations long enough for them to coalesce and rotate as well.…”
Section: Recrystallizationmentioning
confidence: 99%
“…However, in a more recent study Miettinen concluded that that even highly deformed (up to a 50% reduction) near-eutectic SnAgCu solders do not recrystallize statically when annealed at 100 C after deformation at room temperature [71]. Korhonen et al also failed to observe recrystallization in dynamic fatigue tests performed at room temperature [72]. All these results indicate that recovery is effective also in near-eutectic SnAgCu solder alloys.…”
Section: Restoration Of Tin-rich Solder Alloysmentioning
confidence: 99%
“…3 is typical of this system; it has been previously concluded that this microstructure corresponds to recrystallization of the highly deformed Sn near the crack region. 15,16 This previous study of room-temperature fatigue also examined the relation between room-temperature fatigue lifetimes and orientations of singleSn-grained solder joints. 15 Figure 4a shows the inverse pole (IP) figure (equal-area projection) of all the single Sn grains determined by electron backscatter diffraction (EBSD); the number on each symbol in the figure reflects the relative lifetime of the individual solder ball (smaller numbers correspond to longer lifetimes, with sample 1 corresponding to a lifetime of 711.5 cycles).…”
Section: Room-temperature Fatiguementioning
confidence: 99%